The outline of the activities of the Polish Nurses Association in Elbląg - Sobczak, Marzena; Dybikowska, Katarzyna (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. The Polish Nurses Association has undergone constant changes since the moment of its establishment in 1957. Depending on the region in the country, these changes have occurred with a different intensification. Unfortunately, some of the periods of the activities of the Association are passing into oblivion. The nurses who made history of the Association are passing away and the documents are not properly stored. Aim of the study. The aim of the paper is to present the activities of the Polish Nurses Association in Elblag. Materials and methods. Both the people and the documents constituted the research material. The research has been conducted on the basis of the interview and the document analysis. Results and conclusions. The political and administrative changes occurring in Poland have had a great impact on the establishment and the activities of the Polish Nurses Association in Elblag as well as the changes in the legislature concerning the nursing profession.